2017
DOI: 10.1073/pnas.1711744114
|View full text |Cite
|
Sign up to set email alerts
|

Ultralow thermal conductivity in all-inorganic halide perovskites

Abstract: Controlling the flow of thermal energy is crucial to numerous applications ranging from microelectronic devices to energy storage and energy conversion devices. Here, we report ultralow lattice thermal conductivities of solution-synthesized, single-crystalline all-inorganic halide perovskite nanowires composed of CsPbI (0.45 ± 0.05 W·m·K), CsPbBr (0.42 ± 0.04 W·m·K), and CsSnI (0.38 ± 0.04 W·m·K). We attribute this ultralow thermal conductivity to the cluster rattling mechanism, wherein strong optical-acoustic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
360
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 309 publications
(387 citation statements)
references
References 41 publications
24
360
1
2
Order By: Relevance
“…A novel guideline concept, phonon-glass and electron-crystal, is proposed to optimize thermoelectric performance (Slack and Rowe, 1995;Beekman et al, 2015). The previous studies have demonstrated that host-guest systems are ideal platform for this concept, such as clathrates (Takabatake et al, 2014), perovskites (Lee et al, 2017), and skutterudites (Ren et al, 2017), in which the lattice thermal conductivity (κ l ) can be dramatically reduced to a glass-like value while maintaining excellent electric properties. Because of their desirable thermoelectric behaviors, host-guest systems are identified as one of the most promising materials in practical thermoelectric applications.…”
Section: Introductionmentioning
confidence: 99%
“…A novel guideline concept, phonon-glass and electron-crystal, is proposed to optimize thermoelectric performance (Slack and Rowe, 1995;Beekman et al, 2015). The previous studies have demonstrated that host-guest systems are ideal platform for this concept, such as clathrates (Takabatake et al, 2014), perovskites (Lee et al, 2017), and skutterudites (Ren et al, 2017), in which the lattice thermal conductivity (κ l ) can be dramatically reduced to a glass-like value while maintaining excellent electric properties. Because of their desirable thermoelectric behaviors, host-guest systems are identified as one of the most promising materials in practical thermoelectric applications.…”
Section: Introductionmentioning
confidence: 99%
“…With the reduced dimensions, some inherent natures like band structure and photon transport will behave differently. For example, reduced thermal conductance from the enhanced boundary scattering, together with the improved Seebeck coefficient from the modified energy band, makes low‐dimensional perovskites potential materials for thermoelectrics . Recently, Wang et al have investigated the cation dynamics governed by thermal properties in different types of perovskite nanowires .…”
Section: Discussionmentioning
confidence: 99%
“…e) Thermal conductivity of MAPbX 3 as a function of temperature. Reproduced with permission . Copyright 2018, American Chemical Society.…”
Section: Lasing Based On Lhp‐ncsmentioning
confidence: 99%
“…f) Temperature dependence of thermal expansion d L / L 0 of MAPbX 3 . Reproduced with permission . Copyright 2018, American Chemical Society.…”
Section: Lasing Based On Lhp‐ncsmentioning
confidence: 99%
See 1 more Smart Citation